Diffusion of particles adsorbed on a triangular lattice: Pairwise and three-particle interactions - Tarasenko, Alexander A. (2003)
In the present paper, the influence of both pairwise and three-particle interactions on the mobility of adsorbed particles diffusing on a lattice with triangular symmetry has been studied. Two different techniques has been used for describing the surface diffusion phenomenon. On one hand, explicit expressions for the chemical and jump diffusion coefficients have been calculated by using real-space renormalization group (RSRG) approach. A number of the RSRG transformations with blocks of different sizes and symmetries have been investigated. In particular, it has been shown that the precision of the method depends strongly not only on the number of sites in the RSRG blocks but also on their composition and structure. On the other hand, numerical simulations by using the Monte Carlo scheme has been used to simulate the process of particle migration. Using both methods, adsorption isotherms for different temperatures and the coverage dependencies for the thermodynamic factor and the chemical diffusion coefficient have been calculated. The behavior of the above mentioned quantities has been compared when the adparticles interact via only either pairwise or three-particle interactions. Despite the fact that both methods constitute very different approaches, the correspondence of numerical data with analytical results is surprisingly good. Therefore, it can be concluded that the RSRG method can be successfully applied for lattice gas systems to characterize the thermodynamic and kinetic properties of strongly interacting adsorbates.